Sitting as a moral practice: Older adults' accounts from qualitative interviews on sedentary behaviours. Issue 9 (1st November 2021) - Palmer, Victoria J.; Gray, Cindy M.; Fitzsimons, Claire; Mutrie, Nanette; Wyke, Sally; Der, Geoff; Chastin, Sebastien F. M.; Skelton, Dawn A.
Abstract: Amidst public health campaigns urging people to sit less as well as being more physically active, this paper investigates how older adults make sense of their sedentary behaviour. Using an accounts framework focusing on how people rationalise their sitting practices, we analysed data from 44 qualitative interviews with older adults. All interviewees had received information about sedentary behaviour and health, visual feedback on their own objectively measured sitting over a week and guidance on sitting less. Participants used accounts to position sitting as a moral practice, distinguishing between 'good' (active/'busy') and 'bad' (passive/'not busy') sitting. This allowed them to align themselves with acceptable (worthwhile) forms of sitting and distance themselves from other people whose sitting they viewed as less worthwhile. However, some participants also described needing to sit more as they got older. The findings suggest that some public health messaging may lead to stigmatisation around sitting. Future sedentary behaviour guidelines and public health campaigns should consider more relatable guidelines that consider the lived realities of ageing, and the individual and social factors that shape them. They should advocate finding a balance between sitting and moving that is appropriate for each person.